Medicamentos judicializados na região central do estado do Rio Grande do Sul - Reinheimer, Isabel Cristina (2014)
Brazilian society experiences a substantial increase in the consumption of drugs and conflicts involving access to these therapeutic resources. In the judicial sphere, processes directed towards access to medicines and pharmaceutical inputs are called drug legalization. Actions involving this issue have been growing at exponential proportions throughout Brazil, especially in Rio Grande do Sul. This leads to numerous consequences to the Unified Health System (SUS) highlighting the impact on the public health budget. From this assumption, the present study aims to investigate the judicialized drugs that remained stored without use, after completion of judicial determination, generating waste of public money. Adding to this, will seek to outline the profile of this stock with emphasis on drugs that are not part of the SUS lists, comparing them to the options that are available in the public health system. This research follows the cross-sectional design and was based on RAME 030 reports filed with the Pharmaceutical Assistance sector of a Regional Health of Rio Grande do Sul. Results demonstrated that 889 drugs were judicialized and remained stored in the Central Region of Rio Grande do Sul. Majority (73.23%) are medicines "Outside of SUS Lists". From a sampling (in descending frequency analysis) were selected 45 drugs "Out of the SUS lists" that were judicialized and remained stocked in, at least, ten of the 31 cities surveyed. Judicialized these drugs, 91.11% had alternatives with identical or similar SUS anatomical, therapeutic and chemical properties. From this, it follows that it is imperative to establish strategies for continuing education to professionals and health managers about products available in SUS and how to access them. Finally, considering the political and public resources, it becomes necessary to adopt rational criteria and a careful analysis of the legalization of drugs. This refers to interinstitutional and multidisciplinary conduct in order to establish effective channels of communication between health and justice.